Inclusive Business Practices in Tourism: Evidence from Hotels and Restaurants in Labuan Bajo Inclusive Business Practices in Tourism: Evidence from Hotels and Restaurants in Labuan Bajo - I Nengah dasi Astawa; Reynaldo Angga Siagian; Ni Wayan Noviana Safitri; Roseven Rudiyanto; Marius Yosef Seran Seran; Teddy Halim (Jurnal Penelitian Terapan Mahasiswa, 2026)
This study aims to analyze inclusive tourism practices in the hotel and restaurant/café sectors in Labuan Bajo using a multidimensional approach covering economic, socio-cultural, environmental, and infrastructure aspects. A mixed-method approach was employed, with data collected through observations, surveys, and interviews. Quantitative data were analyzed descriptively, while qualitative data were examined using thematic analysis to strengthen the findings. The results indicate that the economic dimension is the most dominant, particularly in terms of local employment absorption, market access, and participation in local supply chains. However, the social, environmental, and infrastructure dimensions remain underdeveloped, as reflected in the limited inclusion of marginalized groups, insufficient integration of local culture, and suboptimal environmental management practices and accessibility. Overall, the implementation of inclusive tourism in Labuan Bajo is still partial and largely focused on economic aspects. Therefore, more comprehensive efforts are needed to strengthen social, environmental, and infrastructure dimensions to promote more inclusive and sustainable tourism development.